CN77 EONS advocacy toolkit: How to let your voice be heard as a cancer nurse - Protogiros, Dimitrios; van Klinken, M.V.; Suchodolska, G.; Tsitsi, Theologia; Catania, G.; Knötgen, G. (My University, 2023)
Cancer nurses are at the heart of cancer care and experience the rapidly changing conditions and the influence of health politics in their daily practice. These are some of the reasons why there needs to be leaders who can uniquely and effectively promote policy and social change in cancer. Recognising the lack of a document on cancer nursing advocacy, the European Oncology Nursing Society’s (EONS) Advocacy Working Group developed a guide aimed at addressing the need for individuals and organisations in cancer to better understand the advocacy concept and for a successful approach to sustainable advocacy.